Pelatihan Pembuatan Makanan Yōshoku Sebagai Ide Bisnis UMKM Kepada SML UMKM Centre - Chaiyadi, Maudy Sausan (Jurnal Abdimas Pariwisata, 2024)
Training on Making Yōshoku Cuisine as SME Business Idea for SML UMKM Centre Community Service (PkM) is carried out with the aim of raising awareness and providing beneficial knowledge and skills to the community. This PkM activity is directed towards the SML UMKM Centre, a business development facility established by Sinar Mas Land. SML UMKM Centre provides various facilities to support the development of SMEs. In this PkM activity, the executing team will conduct training on making Yōshoku cuisine, a fusion of Japanese and Western flavours. The training aims to provide knowledge about Yōshoku food menus as ideas for starting SME food businesses for the SML UMKM Centre community, namely Alfredo Gyoza and Nanban Chicken Rice Bowl. The executing team will deliver detailed presentations on the foods to be made, including in-depth explanations of the recipes to be used and the stages of preparation. Organizing this training it is expected to provide an opportunity for participants to be creative in creating Yōshoku dishes as a new opportunity in the culinary business.